2002
DOI: 10.1128/mcb.22.12.4181-4188.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ras and the Mitogen-Activated Protein Kinase Pathway Promotes Protein Degradation in Muscle Cells of Caenorhabditis elegans

Abstract: To discover and study intracellular signals that regulate proteolysis in muscle, we have employed transgenic strains of Caenorhabditis elegans that produce a soluble LacZ reporter protein limited to body-wall and vulval muscles. This reporter protein is stable in well-fed wild-type animals, but its degradation is triggered upon a shift to 25°C in a strain carrying a temperature-sensitive activating mutation in the Ras oncogene homologue let-60. These mutants are not physiologically starved, inasmuch as growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 60 publications
2
76
0
Order By: Relevance
“…C-myc, a proto-oncogene, is believed to be one of the candidate oncogenes, the abnormal expression of cmyc caused oncogene activation, promoting tumour development. Studies have shown that the activity of Ras extends the half-life of myc by the accumulation of stable myc protein and activation of Ras Raf MAPK pathway (Szewezyk et al 2002). NF-kB 1 , as a transcription factor protein, may participate in the regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…C-myc, a proto-oncogene, is believed to be one of the candidate oncogenes, the abnormal expression of cmyc caused oncogene activation, promoting tumour development. Studies have shown that the activity of Ras extends the half-life of myc by the accumulation of stable myc protein and activation of Ras Raf MAPK pathway (Szewezyk et al 2002). NF-kB 1 , as a transcription factor protein, may participate in the regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Ras/MAPK pathway has also been shown to promote protein degradation in C. elegans muscles, leading to a progressive loss of motility (Szewczyk et al 2002). We therefore investigated whether gla-3 might influence muscle-protein degradation through its interaction with the Ras/MAPK pathway.…”
Section: Gla-3 Is a Negative Regulator Of The Mapk Signaling Pathway mentioning
confidence: 99%
“…Proper focal depth was achieved utilizing a custom plastic housing designed by Dr Conley for the ProScope, with oblique incident illumination. Videos were used to determine movement rates using the previously described swim test (Szewczyk et al, 2002). Ten randomly selected animals from each condition were evaluated, and the movement rate of each animal was measured 10 times.…”
Section: Movement Assaymentioning
confidence: 99%